1999
DOI: 10.1577/1548-8667(1999)011<0312:feosso>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Field Exposure of Seven Species or Subspecies of Salmonids toMyxobolus cerebralisin the Colorado River, Middle Park, Colorado

Abstract: Recent failures in recruitment of rainbow trout Oncorhynchus mykiss in the Colorado River in Middle Park, Colorado, USA, led to studies of the effect of the myxosporean parasite Myxobolus cerebralis, the causative agent of whirling disease, on the wild trout fishery in the river. conducted field exposures of sentinel fish to examine the vulnerability of seven species or subspecies of salmonids exposed to the parasite in the Colorado River. During 1995-1996, brook trout Salvelinus fontinalis and Colorado River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 25 publications
4
64
2
Order By: Relevance
“…Two locations were immediately downstream of Windy Gap Reservoir in the 'Spill Basin' and in the alternate outlet channel that we termed the 'North Outlet'. These were necessary choices to deter- (Thompson et al 1999). This was also where all fish were held after the initial exposure period at different locations, since it remains ice-free during the winter months.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two locations were immediately downstream of Windy Gap Reservoir in the 'Spill Basin' and in the alternate outlet channel that we termed the 'North Outlet'. These were necessary choices to deter- (Thompson et al 1999). This was also where all fish were held after the initial exposure period at different locations, since it remains ice-free during the winter months.…”
Section: Methodsmentioning
confidence: 99%
“…A 'block' consisted of two 3.7 m livestock feed troughs, each modified into a flow-through floating tank with 4 quadrant cells (see Thompson et al 1999), and tethered adjacently in the river. One cell of each tank was randomly chosen to hold the test fish to obtain 2 replicates at each exposure location.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explana tion of this inconsistent production of antibodies is that myxozoans may mimic antigens of host fish (Pauley, 1974). Acquired resistance to reinfection with PKD and whirling disease has been documented (Klontz et al, 1986;Foott and Hedrick, 1987;Hedrick et al, 1998) Introduction of the resistant strains The genetic resistance of certain salmonid fish spe cies or strains to C. shasta and M. cerebralis have been reported (Bartholomew, 1998;Hedrick et al, 1999aHedrick et al, , 1999Thompson et al, 1999). However, salmonid strains resistant to C. shasta were found to be suscep tible to M. cerebralis, suggesting that the mechanisms of resistance are different for the two myxozoans (Hedrick et al, 2001).…”
Section: Chemotherapymentioning
confidence: 99%
“…During the 1990s, numerous investigations that included water filtration studies to estimate TAM production (Thompson & Nehring 2000, Nehring et al 2003, aquatic oligochaete studies (Zendt & Bergersen 2000) and sentinel fish exposure experiments (Thompson et al 1999 demonstrated that Windy Gap Reservoir (WGR) in Grand County, Colorado, was a major point source of M. cerebralis infectivity and a primary factor in the WD epizootic that decimated the wild rainbow trout population in the upper Colorado River downstream of the reservoir (Nehring & Thompson 2001, Nehring 2006. Between April 1997 and March 1998 and April 1998 and March 1999, total annual numbers of TAMs in the discharge from WGR were estimated to be 960 × 10 9 and 1.8 × 10 12 , respectively .…”
Section: Discussionmentioning
confidence: 99%